Sources and interpretation in ancient Judaism studies for Tal Ilan at sixty - Pioṭrḳovsḳi, Meron M. 1977-; Herman, Geoffrey 1967-; Dönitz, Saskia 1973-; Ilan, Ṭal 1956- (Leiden Boston Brill, 2018)
Front Matter -- Copyright Page -- Preface and Acknowledgements -- Abbreviations -- Notes on Contributors -- Tabula Gratulatoria -- Introduction -- Second Temple Literature and History -- Chasing Away Lions and Weaving: The longue durée of Talmudic Gender Icons /Yosef Garfinkel -- Malthace, Archelaus, and Herod Antipas: Between Genealogy and Typology /Daniel R. Schwartz -- A New Perspective on Two Jewish Queens in the Second Temple Period: Alexandra of Judaea and Helene of Adiabene /Etka Liebowitz -- Was Hillel a Pharisee? /Cana Werman -- The Jews and the Papyri -- Ezechiel 33,21–39,29: Anmerkungen zum Profil der Sinneinheit in der nicht-masoretischen Textfassung (Papyrus 967) und zu Veränderungen durch proto-masoretische Redaktoren /Karin Finsterbusch -- The Third Century BCE: New Light on Egyptian Jewish History from the Papyri /Noah Hacham -- ‘Literary Jews:’ The Jewish Community of Oxyrhynchus in Light of Non-documentary Texts on Papyrus /Meron M. Piotrkowski -- Shabtai in Egypt: Cultural Interaction between Jews and Egyptians under the Ptolemies /Zsuzsanna Szántó -- Rabbinic Literature -- Babylonia of Pure Lineage: Notes on Babylonian Jewish Toponymy /Geoffrey Herman -- A Spindle for Caesar’s Daughter /Reuven Kiperwasser -- Rabbinic Forensics: Distinguishing Egg White from Semen in born Giṭṭin 57a /Judith R. Baskin -- Rabbinic Images of Second Temple Diasporas and Their Links with Judaea: History or Fantasy? /Isaiah Gafni -- Are Parables an Interpretation? /Ronit Nikolsky -- When a Man Sells His Daughter as an ‮אמה‬: The ‮אמה העבריה‬ as m. Qiddushin’s Role Model for Becoming a Wife /Judith von Bresinsky -- Classroom Encounters—An Appreciation /Christiane Hannah Tzuberi -- List of Publications of Prof. Tal Ilan.
Sources and Interpretation in Ancient Judaism: Studies for Tal Ilan at Sixty , a collection of studies by 14 scholars, is designed to honor an outstanding scholar in the field of Ancient Judaism, Tal Ilan. These studies reflect realms within the broad field of Ancient Judaism that are central to Ilan’s scholarship: Second Temple literary sources and history, Gender, Jewish papyrology and rabbinic literature. The studies within this volume are of an interdisciplinary nature, offering new readings and interpretations of known sources such as Josephus and rabbinic texts, but also introducing the reader to an entirely new body of sources, namely Jewish papyri. The volume therefore aims to introduce specialists and non-specialists to new fields of research
Keywords: Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Judaism -- History -- Talmudic period, 10-425; Jews -- History -- 586 B.C.-70 A.D; Jews -- History -- 70-638; Festschrift